2011
DOI: 10.1002/ana.22400
|View full text |Cite
|
Sign up to set email alerts
|

Acid β‐glucosidase mutants linked to gaucher disease, parkinson disease, and lewy body dementia alter α‐synuclein processing

Abstract: Objective: Heterozygous mutations in the GBA1 gene elevate the risk of Parkinson disease and dementia with Lewy bodies; both disorders are characterized by misprocessing of a-synuclein (SNCA). A loss in lysosomal acid-bglucosidase enzyme (GCase) activity due to biallelic GBA1 mutations underlies Gaucher disease. We explored mechanisms for the gene's association with increased synucleinopathy risk. Methods: We analyzed the effects of wild-type (WT) and several GBA mutants on SNCA in cellular and in vivo models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

15
274
1
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 294 publications
(291 citation statements)
references
References 43 publications
15
274
1
1
Order By: Relevance
“…N370S appears to confer a milder reduction in GCase activity 46. In PD, however, both GBA loss‐of‐function and toxic gain‐of‐function hypotheses have been proposed 5, 47. In cultured cells, mutant GBA promoted α‐synuclein accumulation in a dose‐dependent manner without observed loss of GCase function 47.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…N370S appears to confer a milder reduction in GCase activity 46. In PD, however, both GBA loss‐of‐function and toxic gain‐of‐function hypotheses have been proposed 5, 47. In cultured cells, mutant GBA promoted α‐synuclein accumulation in a dose‐dependent manner without observed loss of GCase function 47.…”
Section: Discussionmentioning
confidence: 99%
“…In PD, however, both GBA loss‐of‐function and toxic gain‐of‐function hypotheses have been proposed 5, 47. In cultured cells, mutant GBA promoted α‐synuclein accumulation in a dose‐dependent manner without observed loss of GCase function 47. However, in PD patients heterozygous for a GBA mutation, GCase activity is reduced in induced pluripotent stem‐cell–derived neurons,48 brain,45 cerebrospinal fluid,48 and blood 37.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown in SH‐SY5Y cell cultures, neuronal cultures, conduritol‐β‐epoxide (CβE)‐treated mice, and transgenic Gba1 mouse models that reduced GCase activity results in increased α‐synuclein levels 7, 8, 9, 10, 11, 12, 13, 14. Conversely, it has been demonstrated in cell models that increased α‐synuclein causes a decrease in GCase activity 15.…”
mentioning
confidence: 99%
“…Additionally, Cullen et al (2011) showed that when wild type or mutant GBA1 is co-expressed with α -synuclein in MES23.5, PC12, and HEK293 cell lines, α -synuclein accumulation increased only in the mutant GBA1 cell lines, but not in the wild type. In another study, accumulation of α -synuclein increased in cultured cells and the SN of mice following treatment with conduritol B epoxide, a GCase inhibitor (Manning -Bog et al, 2009 ).…”
Section: Gba1 Mutations and Lewy Body Pathologymentioning
confidence: 99%
“…However, this speculation is probably an over-simplified view, because conflicting results exist. For example, treatment of the model used by Cullen et al (2011) with conduritol B epoxide does not increase α -synuclein protein levels.…”
Section: Gba1 Mutations and Lewy Body Pathologymentioning
confidence: 99%